ANALISIS TENTANG PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP FUNGSI PARTAI POLITIK SEBAGAI SARANA KOMUNIKASI - Antonigiar anjar febriansyah; Sri Erlinda; Hambali ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is backgrounded by the function of political parties as a means of communication which is the responsibility of political parties itself to run it. The formulation of the problem in this study is How university of Riau students’ Perceptions Towards the Function of Political Parties as a means of communication? The purpose of this study is to determine the perception of University of Riau Students towards the Function of Political Parties as a means of communication. The population of this research are the students of Riau University with the number of students are 27.268 students and the writer chose 180 students as the sample. The data collection instrument is a questionnaire consisting of 17 questions. The interview consisted of 17 questions. This research use Qualitative Descriptive Analysis. The formulation of the hypothesis formulated i.e. University of Riau Students’ perception towards the Function of Political Parties as a Means of Communication is in good category. The result of this study shows that from 180 respondents there were 6.67% falls into not good category, 28.43% were in the less good category, 46.31% were in good category, and 18.59% were in very good category. Then the results of hypothesis testing can be accepted.Keywords:Perception, Political Party